Avoiding Crowded Places During COVID-19: Common Sense or a Complex Strategic Decision? - Stroom, Martijn; Eichholtz, Piet; Kok, Nils (Frontiers in Psychology, 2021)
Introduction: Following a period of strict lockdowns during the COVID-19 pandemic, most countries introduced policies in which citizens were expected to avoid crowded places using common sense, as advised by the WHO. We argue that the ambiguity in the recommendation to “avoid crowded places” implicitly forces individuals to make a complex strategic decision. Methods: Using a Dutch representative sample of 1,048 participants [42% male, mean age = 43.78 years (SD=12.53), we examine the effect of context on the decision to visit a hypothetical recreational hotspot under the policy recommendation to “avoid crowded places”. We randomize four levels of context on the crowdedness “on the streets” (no context, low, medium, and high context). Subsequently, participants are asked to estimate the percentage of others going out in the same situation. Finally, we assess the impact of a selection of personal characteristics on the likelihood of visiting a crowded place. Results: Respondents are proportionally more likely to go in a low context and high context, compared to no context (diff = .121, p<.000, and diff = .034, p<.05, respectively) and middle context (B; diff = .125, p<.000, and diff = .037, p<.05, respectively). Low context information also decreases the expectation of others going out (-2.63%, z = 4.68, p<.000). High context information increases the expected percentage of others going out (significant only for medium to high context; 2.94%, z=7.34, p<.001). Furthermore, we show that education, age, and health and risk attitude are all predictive of the likelihood to visit a crowded place, notwithstanding the context. Discussion: Although there is a strong inclination to avoid crowded places during the COVID-19 pandemic (81%), we find two context-driven exceptions: when people expect to avoid crowded spots (in the “low” context, i.e. strategical decision-making) and when people expect others to go (social influence). The freedom provided by ambiguous public policy is implicitly asking more from the population than it initially seems. “Use your common sense” is often the accompanied advice, but our results show that more and better information concerning the context is essential to enable us to make an optimal decision for ourself, and for society.